Leber’s Hereditary Optic Neuropathy Plus Causing Recurrent Myelopathy due to an MT-DN1 Mutation at G3635A - Elijah Lackey; Ariel Lefland; Christopher Eckstein (Case Reports in Neurological Medicine)
A 51-year-old man with known Leber’s hereditary optic neuropathy (LHON) presented with worsening lower extremity weakness and numbness. Following an episode of myelopathy two years before, he had been ambulating with a walker but over two weeks became wheelchair bound. He also developed a sensory level below the T4 dermatome to light touch, pinprick, and vibration. MRI of his cervical and thoracic spine showed a nonenhancing T2 hyperintense lesion extending from C2 to T12. At his presentation two years earlier, he was found to have a longitudinally extensive myelopathy attributed to his LHON. Genetic testing revealed a 3635 guanine to adenine mutation. MRI at that presentation demonstrated a C1-T10 lesion involving the central and posterior cord but, unlike the new lesion, did not involve the ventral and lateral horns. Given the similarity to his prior presentation and a negative evaluation for alternative etiologies, he was thought to have recurrent myelopathy secondary to Leber’s Plus. To our knowledge, recurrent myelopathy due specifically to the G3635A mutation in Leber’s Plus has not been reported previously.